Preparation method of formed coke special for ferrosilicon alloy
By preparing the special type of coordinating silicon iron alloy, the lack of special focus in the existing technology has been solved, and high -efficiency and low -cost silicon iron alloy smelting is achieved, which improves yield and quality, and reduces environmental pollution.
Patent Information
- Application Number
- CN202411398411.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-28
AI Technical Summary
The existing technology lacks special ferrosilicon cokes for ferrosilicon alloys specifically used in ferrosilicon alloy smelting, which cannot meet the high quality and high efficiency needs of ferrosilicon alloy production.
By crushing and screening the coking plant, combined with inorganic and organic adhesives, the dedicated coke of silicon iron alloys is prepared after stirring, water adding, pressed into balls and drying. The component and structural design of this type of coke can provide high -fixed carbon content, low ash score, low wave score and high resistance to meet the demand for smelting of silicon iron alloy.
This silicon iron alloy special scorch can not only replace some coke, provide the required silicon raw materials, improve the output of silicon iron alloys, reduce production costs, improve smelting efficiency, and reduce environmental pollution.
Smart Images

Figure BDA0005074478210000071 
Figure BDA0005074478210000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ore-fired furnace smelting, and in particular to a method for preparing special coke for ferrosilicon alloy. Background Art
[0002] Submerged arc furnace is mainly used for smelting silicon, manganese, chromium and other ferroalloys, calcium carbide and yellow phosphorus. It can be divided into ferrosilicon furnace, ferromanganese furnace, calcium carbide furnace, etc. according to product classification. Its working characteristics are that it uses carbon or magnesium refractory materials as furnace lining, and uses self-training electrodes to heat, melt and reduce the oxides in the ore in the furnace by the resistance heat generated by the current passing through the charge, so as to obtain ferroalloy products. Most of my country's ferroalloy production enterprises are in the western region. In recent years, with the tightening of national environmental protection policies, the rectification of environmental pollution, and the complete closure of energy-intensive, low-efficiency and small-capacity enterprises, submerged arc furnaces must respond to the national call to reduce energy consumption and increase product output and quality in order to survive.
[0003] Due to the tight supply and high price of ferroalloy coke, the production cost of the ferroalloy industry remains high. Ferroalloy coke and electricity account for about 45%-55% of the production cost of ferroalloys. If molded coke can replace part of ferroalloy coke, it will be of great significance for ferroalloy enterprises to significantly reduce costs.
[0004] At present, ferroalloy coke can be divided into two categories, namely charcoal and coke. The main component of charcoal is carbon, with very low ash content, calorific value of about 30.3MJ / kg, large specific resistance (generally greater than 8000Ω·mm2 / m), and good chemical activity. Charcoal can be made by kiln burning and dry distillation. Charcoal is a very good reducing agent. It has a large specific resistance, a large porosity, poor graphitization performance, and good chemical activity. It is the best reducing agent. But it is expensive and the source is insufficient. Only when smelting special ferroalloys, a small amount of charcoal is used. Therefore, metallurgical coke of coke is still the main reducing agent for the production of ferroalloys. As a carbonaceous reducing agent for the production of ferroalloys, metallurgical coke generally has the disadvantages of high ash content, low reaction activity and specific resistance, resulting in high power consumption; at the same time, metallurgical coke is in short supply and its price is high, which seriously affects the economic benefits of ferroalloy enterprises. The smelting of different types of ferroalloys has different requirements for ferroalloy coke. The production of ferrosilicon alloys has the highest requirements for the quality of alloy coke. Therefore, ferroalloy coke that meets the requirements of ferrosilicon alloy production can generally meet the requirements of other ferroalloy production. The requirements of ferrosilicon alloy production for ferroalloy coke include: high fixed carbon content, low ash content, low content of harmful substances in the ash such as aluminum oxide and phosphorus pentoxide, good reactivity, high resistivity, especially high temperature resistivity, low volatile matter, appropriate strength and blockiness, and low and stable moisture. In the production process of ferroalloy coke, the main factors and measures that affect and improve the properties of ferroalloy coke include three aspects. The first is the influence of coal quality. Under certain coking temperature and coking time conditions, the degree of graphitization of coke depends on the quality of the blended coal. Coke made from weakly bonded coal with poor metamorphism and high volatile content has a low degree of graphitization, high high temperature resistance, and good reactivity. For example, the coke made from gas coal has a porosity of 47% and a resistivity of 2000-2800×10 -6 Ω.m, the α% value is 54.5% at 1100℃, which is used for smelting ferrosilicon. The productivity of electric furnace is increased by 10%, the Si recovery rate is increased by 4.5%, and the unit power consumption is reduced by more than 4.4%. The second is the influence of coking time and coking temperature. The coal material turns to graphitization during the high-temperature coking process. With the increase of temperature and the extension of the residence time at high temperature, the distance between the carbon atomic layers decreases, the arrangement order increases, and the crystals gradually grow, that is, the degree of graphitization increases. Since the coke produced by large coke ovens has a high coking temperature, a long coking time, a thick coal seam, and a high pressure, the coke has a high degree of graphitization and a low resistivity (1500-2200×10 -6 Ω.m), low porosity (<42.9%), poor reactivity (<37%), and therefore not suitable for ferroalloy production. Therefore, lowering the coking temperature and shortening the coking time are conducive to reducing the degree of graphitization and increasing the resistivity. (The coking methods and characteristics of ferroalloy coke are opposite to those of metallurgical coke.) The third is the effect of ash and volatile matter on resistivity. In general, coke with high ash and volatile matter has high resistivity, but the ash and volatile content affect carbon fixation, so it should be considered comprehensively.
[0005] In summary, the following problems exist in the prior art: the current coke is not specially tailored for ferrosilicon alloy smelting, can meet various index requirements, and can also provide siliceous raw materials, reduce the front-end siliceous raw material input, or increase the output of ferrosilicon alloy. Summary of the invention
[0006] The invention provides a method for preparing a special type of coke for ferrosilicon alloy, so as to solve the problem that there is no special type of coke for ferrosilicon alloy tailored for ferrosilicon alloy smelting.
[0007] To this end, the present invention provides a method for preparing a special type of coke for ferrosilicon alloy, comprising the following steps:
[0008] S1: crushing and sieving the coke diced from the coking plant to obtain coke powder of a set particle size to meet the particle size requirements of molding;
[0009] S2: using a belt scale to accurately weigh a certain amount of inorganic binder, organic binder, crushed coke diced in a coking plant, dedusted coke powder or carbon powder obtained by flotation of gravity dedusted ash from an ironmaking blast furnace, and mixing them evenly in a certain proportion using a mixer;
[0010] S3: adding an appropriate amount of water to the mixture obtained in step S2 and further stirring and mixing;
[0011] S4: The mixture obtained in step S3 is pressed into balls using a pair of rollers, and dried in a vertical drying tower for 4 hours. After drying, the mixture is sent to a finished product bin to obtain special coke for ferrosilicon alloy production.
[0012] Furthermore, in step S1, the particle size of the coke powder after crushing is less than 3 mm.
[0013] Furthermore, in step S2, the inorganic binder includes one or more of red iron oxide, sodium bentonite, calcium magnesium powder, solid water glass, slag powder, steel slag powder, lime powder, silica fume, fly ash, and cement.
[0014] Furthermore, the content of red iron oxide Fe2O3 should be greater than 98%.
[0015] Furthermore, the modulus of solid water glass is 2.2-3.5.
[0016] Furthermore, the fineness of the inorganic binder powder is required to meet the requirement that the residue on a 200-mesh sieve is greater than 90%, and the slag powder is required to be above S95 grade.
[0017] Furthermore, the organic binder includes one or more of pregelatinized starch, oxidized starch, corn starch, carboxymethyl cellulose, hydroxypropyl methyl cellulose, xanthan gum, anionic polyacrylamide, white dextrin, yellow dextrin, polyvinyl alcohol, sodium lignin sulfonate, sodium dodecylbenzene sulfonate, emulsified asphalt, coal tar powder, phenolic resin, styrene acrylic emulsion, VAE emulsion, and epoxy resin.
[0018] Furthermore, the carbon powder obtained by flotation of coke powder from coking plant or gravity dust removal ash from ironmaking has an average moisture content of ≤5%, a fixed carbon content of ≥80%, an ash content of ≤25%, and a volatile matter of ≤3%.
[0019] Furthermore, the temperature of the drying tower is 160° C.-200° C., the drying time is 4 hours, and the moisture content of the finished coke product is ≤2%.
[0020] Furthermore, the pressing into balls is performed at room temperature, the pressure of the roller ball press is 20Mpa-40Mpa, and the specification of the coke after pressing into balls is 20mm-50mm.
[0021] The present invention also provides a special type of coke for ferrosilicon alloy, which is spherical, with a specification of 20mm-50mm, and has the following components: fixed carbon is 75-80%, ash is 18-24%, volatile matter is 3-7%, Al2O3 is 1.2-1.8%, and SiO2 is 15-18%. The moisture content of coke is generally between 6% and 10%, and the moisture content of molded coke is ≤2%.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention can replace part of the coke during the smelting of ferrosilicon alloy, not only providing part of the siliceous raw materials required for the ferrosilicon alloy, but also increasing the output of the ferrosilicon alloy.
[0024] 2. Compared with coke blocks with the same particle size and the same indicators, the present invention has a lower price, a low content of harmful substances in the ash such as aluminum oxide, phosphorus pentoxide, sulfur, etc., good coke reactivity, high resistivity, low volatile matter, good charge permeability, less sparking, and good slag and carbon removal performance.
[0025] 3. Among the binders used in the present invention, the inorganic binder can provide the silicon dioxide required for ferrosilicon alloy smelting, and the organic binder is completely burned out in the high temperature stage without affecting the fixed carbon content of the molded coke. The addition of the organic binder can ensure the cold pressing strength of the molded coke, and the ball forming rate can reach more than 85%, avoiding the damage of the molded coke before drying, while the organic binder ensures the strength increase of the molded coke and still has a high strength at high temperature.
[0026] 4. The present invention has high density, uniform shape, high cold and hot strength, and low heat loss, which is beneficial to reducing breakage during transportation and use; the current is stable during use, which is beneficial to deep insertion of electrodes, and the melting speed of furnace charge is faster, which can achieve a certain degree of energy saving.
[0027] 5. The present invention effectively improves the added value of coke powder from coking plants and gravity dust from ironmaking, realizes the resource utilization of dust from steel plants, effectively reduces the production cost of ferroalloy production enterprises, improves the quality and output of ferrosilicon alloys, and also solves the problem of serious dust pollution to the environment caused by discarded coke powder.
[0028] 6. The present invention has high fixed carbon content, low ash content, less harmful substances in the ash, good reactivity, high high-temperature resistivity and low volatile matter. DETAILED DESCRIPTION
[0029] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the present invention is now described.
[0030] The present invention provides a method for preparing special coke for ferrosilicon alloy, the method comprising the following steps:
[0031] Step 1: crush and screen the coke from the coking plant to meet the particle size requirements for molding;
[0032] Step 2: Use a belt scale to accurately weigh a certain amount of inorganic binder, organic binder and coke diced from a coking plant, dust-removed coke powder or carbon powder obtained by flotation of gravity dust removal ash from an ironmaking blast furnace, and mix them in a certain proportion using a mixer for 10-40 minutes to ensure uniform mixing;
[0033] Step 3: Add appropriate amount of water to the mixture obtained in step 2 and further stir and mix evenly, the mixing time is 10-60 minutes; Step 4: Use a pair of rollers to press the mixture obtained in step 3 into balls, dry it in a vertical drying tower, and then send it to the finished product warehouse to obtain special coke for ferrosilicon alloy production.
[0034] Furthermore, the particle size of the coke powder after crushing in step 1 is less than 3 mm.
[0035] Furthermore, in the step 2, the inorganic binder includes one or more of metakaolin, red iron oxide, sodium bentonite, calcium magnesium powder, solid water glass, slag powder, steel slag powder, lime powder, silica fume, fly ash, and cement; further, the content of red iron oxide Fe2O3 should be greater than 98%; the modulus of solid water glass is 2.2-3.5; the fineness of the inorganic binder powder is required to meet the requirement that the residue on the 200 mesh sieve is greater than 90%; the slag powder is required to be S95 grade or above; the cement is required to be 425 P·Ⅰ and P·Ⅱ cement;
[0036] The organic binder includes one or more of pregelatinized starch, oxidized starch, corn starch, carboxymethyl cellulose, hydroxypropyl methyl cellulose, xanthan gum, anionic polyacrylamide, white dextrin, yellow dextrin, polyvinyl alcohol, sodium lignin sulfonate, sodium dodecylbenzene sulfonate, emulsified asphalt, coal tar powder, phenolic resin, styrene acrylic emulsion, VAE emulsion, and epoxy resin;
[0037] Furthermore, the molecular weight of anionic polyacrylamide must be 8 million and above; the solid content of emulsified asphalt must be above 50%; further, the moisture content of coke powder from coking plant or carbon powder obtained by flotation of gravity dust removal ash from ironmaking should be ≤5%, the fixed carbon content should be ≥80%, the ash content should be ≤25%, and the volatile matter should be ≤3%.
[0038] Furthermore, the mixer in step 2 is a double-shaft mixer, the amount of carbon powder added is 71% from coke powder from a coking plant or flotation of gravity dust ash from ironmaking, the amount of coke diced is 7%, the amount of inorganic binder added is 12.5%, and the amount of organic binder added is 9.5%.
[0039] Furthermore, the pressing into balls in step three is performed at room temperature, the pressure of the roller ball press is 20Mpa-40Mpa, and the specification of the shaped coke is 20mm-50mm.
[0040] Furthermore, the temperature of the drying tower is 160° C.-200° C., the drying time is 4 hours, and the moisture content of the finished coke product is ≤2%.
[0041] Example 1
[0042] A method for preparing a special type of coke for ferrosilicon alloy comprises the following steps:
[0043] S11, 5.31% silica fume, 1.89% red iron oxide, 3.80% calcium magnesium powder, 0.50% slag powder, 7.10% emulsified asphalt, 1.50% polyvinyl alcohol, and 0.90% white dextrin are weighed by belt and added to the dust-removed coke powder and coke dices of the coking plant, and the ratio of coke powder to coke dices is 71:7; the content of red iron oxide Fe2O3 is 98.30%, the slag powder is S95 grade, the solid content of emulsified asphalt is 55.00%, the fixed carbon content of coke powder is 80%, the water content of coke powder and coke dices is 3%, and the amount of water added is 2.5%;
[0044] S12, stirring with a double-roll mixer for 30 min;
[0045] S13, using a pair of rollers to press the balls at a pressure of 25 MPa to produce 30 mm coke, which is then dried in a drying tower at a temperature of 160°C-200°C, for example, at a temperature of 180°C for 4 hours, and then sent to a finished product warehouse after drying.
[0046] In the present invention, the cold strength of the prepared molded coke can reach more than 1000N, the measured strength is 1086N, the hot strength can reach more than 200N at 1000℃, the measured strength is 260N, and it meets the high-temperature smelting strength; because there are organic and inorganic substances in the binder, the organic substances increase the volatile matter, and the inorganic substances increase the ash content. After the two binders are increased, the fixed carbon decreases slightly, and the measured fixed carbon of the molded coke is between 75% and 80%, but after the organic matter is volatilized and released by burning at 300℃, the fixed carbon increases to more than 80%; the measured specific resistivity of coke is 2000μΩ·m, the measured specific resistivity of molded coke is 5702.8μΩ·m, and the reactivity is 45.11. The larger the specific resistivity, the better the electrode for the submerged arc furnace; the moisture content of coke is generally between 6% and 10%, and the moisture content of molded coke is between ≤2%, and the combustion stability is good.
[0047] Example 2
[0048] A method for preparing a special type of coke for ferrosilicon alloy comprises the following steps:
[0049] S21, 4.20% solid water glass, 0.80% sodium bentonite, 1.56% red iron oxide, 2.73% calcium magnesium powder, 1.21% steel slag powder, 5.00% washing oil, 2.56% styrene acrylic emulsion, 1.30% polyvinyl alcohol, 0.39% sodium dodecylbenzene sulfonate, and 0.25% anionic polyacrylamide are weighed by belt and added to the dust-removing coke powder and coke butts of the coking plant, and the ratio of coke powder to coke butts is 71:7; wherein the modulus of solid water glass is 3.0, the content of red iron oxide Fe2O3 is 98.5%, the molecular weight of anionic polyacrylamide is 12 million, the fixed carbon content of coke powder is 85%, the water content of coke powder and coke butts is 2.8%, and the amount of water added is 3.2%;
[0050] S22, stirring with a double-roll mixer for 30 min;
[0051] S23, using a pair of rollers to press the balls at a pressure of 25 MPa to produce shaped coke of a specification of 30 mm, drying it in a drying tower at a temperature of 160°C-200°C, for example, at a temperature of 160°C and a drying time of 4 hours, and then delivering it to a finished product warehouse after drying.
[0052] In the present invention, the cold strength of the prepared molded coke can reach more than 1000N, the measured strength is 1045N, the hot strength can reach more than 200N at 1000℃, the measured strength is 336N, and it meets the high-temperature smelting strength; because there are organic and inorganic substances in the binder, the organic substances increase the volatile matter, and the inorganic substances increase the ash content. After the two binders are increased, the fixed carbon decreases slightly, and the measured fixed carbon of the molded coke is between 75% and 80%, but after the organic matter is volatilized and released by burning at 300℃, the fixed carbon increases to more than 80%; the measured specific resistivity of coke is 2000μΩ·m, the measured specific resistivity of molded coke is 6108.8μΩ·m, and the reactivity is 53.69. The larger the specific resistivity, the better the electrode is for the ore-fired furnace; the moisture content of coke is generally between 6% and 10%, and the moisture content of molded coke is between ≤2%, and the combustion stability is good.
[0053] Example 3
[0054] A method for preparing a special type of coke for ferrosilicon alloy comprises the following steps:
[0055] S31, 5.73% P·Ⅰ type 425 cement, 2.65% fly ash, 0.98% red iron oxide, 1.46% lime powder, 0.68% slag powder, 4.71% coal petroleum asphalt powder, 2.36% pregelatinized starch, 1.12% carboxymethyl cellulose, 0.85% polyvinyl alcohol, and 0.46% sodium dodecylbenzene sulfonate are weighed by belt and added to carbon powder obtained by gravity ash flotation of iron-making blast furnace and coke diced from coking plant, and the ratio of carbon powder to coke diced is 71:7; wherein the fly ash is grade Ⅰ fly ash, the content of red iron oxide Fe2O3 is 99%, the slag powder is grade S105, the fixed carbon content of the carbon powder is 83%, the water content of the carbon powder is 3.5%, the water content of the coke diced is 2.6%, and the amount of water added is 2.6%;
[0056] S32, stirring with a double-roll mixer for 30 min;
[0057] S33, using rollers to press the balls at a pressure of 25 MPa to produce 30 mm coke, which is then dried in a drying tower at a temperature of 160°C-200°C, for example, at a temperature of 170°C for 4 hours, and then sent to a finished product warehouse after drying.
[0058] In the present invention, the cold strength of the prepared molded coke can reach more than 1000N, the measured strength is 1231N, the hot strength can reach more than 200N at 1000℃, the measured strength is 423N, and it meets the high-temperature smelting strength; because there are organic and inorganic substances in the binder, the organic substances increase the volatile matter, and the inorganic substances increase the ash content. After the two binders are increased, the fixed carbon decreases slightly, and the measured fixed carbon of the molded coke is between 75% and 80%, but after the organic matter is volatilized and released by burning at 300℃, the fixed carbon increases to more than 80%; the measured specific resistivity of coke is 2000μΩ·m, the measured specific resistivity of molded coke is 11324.5μΩ·m, and the reactivity is 54.47. The larger the specific resistivity, the better the electrode is for the ore-fired furnace; the moisture content of coke is generally between 6% and 10%, and the moisture content of molded coke is between ≤2%, and the combustion stability is good.
[0059] Example 4
[0060] A method for preparing a special type of coke for ferrosilicon alloy comprises the following steps:
[0061] S41, 3.28% fly ash, 2.43% silica ash, 1.74% red iron oxide, 1.65% steel slag powder, 1.65% slag powder, 0.85% calcium magnesium powder, 4.63% corn starch, 1.15% xanthan gum, 0.67% polyvinyl alcohol, 0.55% sodium lignin sulfonate, and 0.50% styrene acrylic emulsion are weighed by belt and added to the coke powder and coke diced in the coking plant, and the ratio of coke powder to coke diced is 71:7; the fly ash is Class I fly ash, the content of red iron oxide Fe2O3 is 98.3%, the slag powder is S95 grade, the fixed carbon content of coke powder is 84%, the moisture content of coke powder and coke diced is 2%, and the amount of water added is 4%;
[0062] S42, stirring with a double-roll mixer for 30 minutes;
[0063] S43, using a pair of rollers to press the balls at a pressure of 25 MPa to produce shaped coke of a specification of 30 mm, drying it in a drying tower at a temperature of 160°C-200°C, for example, at a temperature of 190°C for 4 hours, and then delivering it to a finished product warehouse after drying.
[0064] In the present invention, the cold strength of the prepared molded coke can reach more than 1000N, the measured strength is 1156N, the hot strength can reach more than 200N at 1000℃, the measured strength is 386N, and the high-temperature smelting strength is met; because there are organic and inorganic substances in the binder, the organic substances increase the volatile matter, and the inorganic substances increase the ash content, after the two binders are increased, the fixed carbon decreases slightly, and the measured fixed carbon of the molded coke is between 75% and 80%, but after the organic substances are volatilized and released by burning at 300℃, the fixed carbon increases to more than 80%; the measured specific resistivity of the coke is 2000μΩ·m, the measured specific resistivity of the molded coke is 8564.3μΩ·m, and the reactivity is 51.98, and the larger the specific resistivity, the better the electrode for the submerged arc furnace; the moisture content of the coke is generally between 6% and 10%, and the moisture content of the molded coke is between ≤2%, and the combustion stability is good.
[0065] The properties and indices of the ferrosilicon alloy special coke obtained in the above embodiments are shown in Table 1 and Table 2 respectively.
[0066] Table 1 Statistical table of performance indicators of special coke for ferrosilicon alloy (composition unit is %)
[0067]
[0068] Table 2 Statistics of the use of special coke for ferrosilicon alloy
[0069]
[0070] As can be seen from Table 1 and Table 2, the ferrosilicon alloy special coke prepared by the present invention has high fixed carbon content, low ash content, low content of harmful substances such as phosphorus, sulfur, aluminum oxide, etc., good compactness, uniform block, high cold strength and hot strength, high resistivity and reactivity, high content of beneficial component silicon dioxide, and can provide the required silicon dioxide raw material during ferrosilicon alloy smelting, thereby achieving the goal of increasing the output of ferrosilicon alloy and reducing the production cost of ferroalloy, and increasing the economic benefits of the enterprise. At the same time, the ferrosilicon alloy special coke is used when the current is stable, which is conducive to deep insertion of electrodes, the melting speed of furnace charge is fast, the slag discharge and carbon discharge are normal, and there is no piercing fire around the electrode, which is not only conducive to the stable operation of the furnace condition of the submerged arc furnace, but also reduces the labor intensity of workers. When the submerged arc furnace is matched with 15% of the ferrosilicon alloy special coke for production, it can effectively reduce the ore consumption, improve the recovery rate of silicon element, and reduce the coke consumption and smelting power consumption simultaneously, and the daily output of ferrosilicon alloy is improved, thereby reflecting that the use of ferrosilicon and this year's special coke can not only achieve certain energy saving, but also effectively improve the output of ferrosilicon alloy, thereby increasing the benefits of the enterprise. In addition, this type of coke effectively improves the added value of coke powder from coking plants and gravity dust ash from ironmaking, realizes the resource utilization of steel plant dust ash, turns waste into treasure, and effectively reduces the production cost of ferroalloy manufacturers with a price advantage lower than other metallurgical cokes, increases the output of ferrosilicon alloys, and also solves the serious dust pollution caused by discarded coke powder to the environment.
[0071] The above description is only an illustrative embodiment of the present invention and is not intended to limit the scope of the present invention. The components of the present invention can be combined with each other without conflict, and any equivalent changes and modifications made by any technician in the field without departing from the concept and principle of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing special coke for ferrosilicon alloy, characterized in that: The method for preparing the special type coke for ferrosilicon alloy comprises the following steps: S1: crushing and sieving the coke diced from the coking plant to obtain coke powder of a set particle size to meet the particle size requirements of molding; S2: using a belt scale to accurately weigh a certain amount of inorganic binder, organic binder, crushed coke diced in a coking plant, dedusted coke powder or carbon powder obtained by flotation of gravity dedusted ash from an ironmaking blast furnace, and mixing them evenly in a certain proportion using a mixer; S3: adding an appropriate amount of water to the mixture obtained in step S2 and further stirring and mixing; S4: The mixture obtained in step S3 is pressed into balls using a pair of rollers, and dried in a vertical drying tower for 4 hours. After drying, the mixture is sent to a finished product bin to obtain special coke for ferrosilicon alloy production.
2. The method for preparing ferrosilicon alloy special coke as claimed in claim 1, characterized in that: In step S1, the particle size of the coke powder after crushing is less than 3 mm.
3. The method for preparing special coke for ferrosilicon alloy as claimed in claim 1, characterized in that: In step S2, the inorganic binder includes one or more of red iron oxide, sodium bentonite, calcium magnesium powder, solid water glass, slag powder, steel slag powder, lime powder, silica fume, fly ash, and cement.
4. The method for preparing ferrosilicon alloy special coke as claimed in claim 3, characterized in that: The content of red iron oxide Fe2O3 should be greater than 98%.
5. The method for preparing ferrosilicon alloy special coke as claimed in claim 3, characterized in that: The modulus of solid water glass is 2.2-3.
5.
6. The method for preparing special ferrosilicon alloy coke as claimed in claim 3, characterized in that: The fineness of the inorganic binder powder is required to meet the requirement that the residue on a 200-mesh sieve is greater than 90%, and the slag powder is required to be above S95 grade.
7. The method for preparing ferrosilicon alloy special coke as claimed in claim 1, characterized in that: The organic binder includes one or more of pregelatinized starch, oxidized starch, corn starch, carboxymethyl cellulose, hydroxypropyl methyl cellulose, xanthan gum, anionic polyacrylamide, white dextrin, yellow dextrin, polyvinyl alcohol, sodium lignin sulfonate, sodium dodecylbenzene sulfonate, emulsified asphalt, coal tar powder, phenolic resin, styrene acrylic emulsion, VAE emulsion, and epoxy resin.
8. The method for preparing ferrosilicon alloy special coke as claimed in claim 1, characterized in that: The carbon powder obtained by flotation of coke powder from coking plant or gravity dust removal ash from ironmaking has an average moisture content of ≤5%, fixed carbon content ≥80%, ash content ≤25%, and volatile matter ≤3%.
9. The method for preparing ferrosilicon alloy special coke as claimed in claim 1, characterized in that: The temperature of the drying tower is 160° C.-200° C., the drying time is 4 hours, and the moisture content of the finished coke product is ≤2%.
10. The method for preparing special ferrosilicon alloy coke according to claim 1, characterized in that: The pressing into balls is carried out at room temperature, the pressure of the roller ball press is 20Mpa-40Mpa, and the specification of the coke after pressing into balls is 20mm-50mm.